Mixopathy - Nishikant N. Gujar; Ashfak Ahmed R. Kakeri; Sajid Ahmed Mudhol (Al Ameen Medical College, 2021)
The government has issued a notification authorizing post-graduate practitioners in specified streams of Ayurveda to be trained to perform surgical procedures i.e., 58 surgeries, a move which has drawn flak from the modern medicine fraternity [1]. The November 20 gazette notification by the Central Council of Indian Medicine (CCIM), a statutory body under the AYUSH Ministry to regulate the Indian systems of medicine, listed 39 general surgery procedures and around 19 procedures involving the eye, ear, nose and throat by amending the Indian Medicine Central Council (Post Graduate Ayurveda Education) Regulations, 2016 [1].